2017
DOI: 10.1080/16066359.2016.1276902
|View full text |Cite
|
Sign up to set email alerts
|

Using video conferencing to deliver a brief motivational intervention for alcohol and sex risk to emergency department patients: a proof-of-concept pilot study

Abstract: Brief motivational intervention (MI) is an efficacious approach to reduce heavy drinking and associated sexual risk behavior among Emergency Department (ED) patients, but the intensity of demands placed on ED staff makes the implementation of in-person MIs logistically challenging. This proof-of-concept pilot study examined the acceptability and logistic feasibility of using video-conferencing technology to deliver an MI targeting heavy drinking and risky sexual behavior to patients in an ED setting. Rigorous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Recent evidence suggests that videoconferencing can be used to deliver evidence-based behavioral counseling at home [[102], [103], [104], [105]], with preliminary results suggesting promise for home-based interventions [106,107]. In a pilot study, we found that we were able to deliver MI with high fidelity using videoconferencing [108]. We believe that using a combination of both videoconferencing and telephone counseling—which allows for easy scheduling of sessions that maximizes patient convenience—may be especially practical and effective.…”
Section: Discussionmentioning
confidence: 96%
“…Recent evidence suggests that videoconferencing can be used to deliver evidence-based behavioral counseling at home [[102], [103], [104], [105]], with preliminary results suggesting promise for home-based interventions [106,107]. In a pilot study, we found that we were able to deliver MI with high fidelity using videoconferencing [108]. We believe that using a combination of both videoconferencing and telephone counseling—which allows for easy scheduling of sessions that maximizes patient convenience—may be especially practical and effective.…”
Section: Discussionmentioning
confidence: 96%
“…However, considering that mHealth intervention efficacy is mixed (Hutton et al, 2020; Kaner et al, 2017; Kazemi et al, 2017) and that this may be due, at least in part, to reduced participant attention and engagement (Lewis & Neighbors, 2015), counselor time allocated to delivering synchronous text-based interventions may be a worthwhile investment. Future research is required to explicitly evaluate how CoAST delivery impacts participant engagement and retention compared to fully automated (text message or web-based), telephone (IVR or one-on-one), videoconference (Celio et al, 2017; King et al, 2020; Lee et al, 2021), and in-person BMIs. Lastly, future research should also seek to understand the impact of these various modes of delivery on intervention utilization, costs, and efficacy outcomes by comparing equivalent content across in-person, videoconference, guided synchronous text-based systems (e.g., CoAST), and fully automated intervention approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those considering implementation might consult a follow-up article in which the study's authors offer suggestions for counsellors derived from content analyses of recorded intervention sessions 2. Planners also should take note of a pilot study in which this intervention was delivered via video-conferencing technology, rather than in person 3. The use of such technology has the potential to increase the utility of the intervention by eliminating the need to train large numbers of staff.…”
Section: Commentarymentioning
confidence: 99%